Surdos e ouvintes : dos bastidores aos aplausos...a busca de autoria em um processo de inclusão pelo teatro - Oliveira, Mirian Martins de (2006)
The work intends to reflect on the ways and possibilities of the inclusion of the deaf in the listening community, using the theater, in a multireferential perspective pointed out by Barbosa and using the action research proposed by Barbier, who recognizes the heterogeneity and the linguistic, socio- cultural and educational aspects of the subjects involved. It also reflects on how this theater, made up of students-deaf actors and listeners, reaches the audience that is composed of the same clientele. It deals with the hypothesis that with theater, in a work in which everyone is involved in a single goal, reflecting and conducting negotiations, inclusion becomes effective. Going through elaborations and constructions of new practices, the subjects cease to be only agents and actors of a system, to assume the role of author of a process of personal and social life, based on the thought of Ardoino. It concludes that from the theatrical games proposed by Reverbel and Spolin and the theater of Boal, which proposes the reflection of the oppressions in search of actions, it is possible the participation of the deaf as a subject, with their differences in culture, identity and language, as pointed out by Skliar, Sá and Carvalho, rescuing the participation not only of them, but of the whole group involved, proposing possible paths for social problems and making possible the exercise of citizenship.